Analisis Hubungan Modal Sosial dengan Partisipasi Masyarakat dalam Pengembangan Desa Wisata Embung Setumpeng, Kabupaten Karanganyar - Sukarno, Lingga Harzaldi; Sugihardjo, Sugihardjo; Wibowo, Agung (Journal of Tourism and Creativity, 2023)
Embung Setumpeng tourism village that located in Mojogedang Regency, Karanganyar Districts is one of community development program that managed by pokdarwis independently. Tourism village development require participation and support from social capital as their main strength. This research goals are to getting know about social capital level, participation level, and the relation between social capital with society participation in developing Embung Setumpeng Tourism Village. This research used quantitative method and the location was selected purposively in Embung Setumpeng Tourism Village, Mojogedang Regency, Karanganyar Districts. Sampling method that used on this research was saturated sampling which all population became the sample. Rank Spearman was used to analyze the data by program IBM SPSS Statistics 25. This research result that high social capital level found on norms, partnership, reciprocity, responsibility, and tolerance. High participation level found on implementation, monitoring and evaluation, also result utilization. Rank Spearman analysis by trust level 95% (α=0,05) found there’s significant relation between trust, norms, relationship, partnership, responsibility, and tolerance with participation level on developing Embung Setumpeng Tourism Village.